Personality traits in children with violent par - Romo P., Nohemi (2008)
In the current investigation is looking to find out more about the features of the recurrent and outgoing personality of children who are having parents who have exerted violence on them, this in another perspective to understand the consequences of domestic violence with him to identify these data, An interview was conducted as well as the implementation and analysis of projective tests of 10 children from two institutions to support children.